Crop production and factor productivities of cotton under rained and irrigated conditions in Kyaukse Area in Myanmar - Ye Win Ko; Perret, Sylvain Roger; Sutat Weesakul; Jourdain, Damien; TICA (Thailand Internati o nal Development Coo peration Agency ) (Pathum Thani, Thailand : Asian Institute of Technology, 2013)
This research investigated cotton production and factor productivities under rain - fed and irrigated conditions in Kyaukse area in Myanmar, where cotton is one of the key economic crop. Kyaukse area receives low amount of annual rainfall. The time series of drought index were calculated by using Standardized Precipitation Index (SPI) from 30 years of historic rainfall data to analyze drought occurrence in this study area. The results show ed that extreme drought event rarely occurred in the study area, severe and moderate drought events are sometimes occurring and mild drought event often occur. The probability of near - normal event occurrence is lower than that of mild drought event and mod erate and very wet events sometimes happened in the study area, whereas in extremely wet events also occur. The AquaCrop model was used to simulate yield response to water under different water stress levels (0 - 50%) based on the deficit irrigation strateg ies. Sensitivity analysis was also performed by using the model to find out the most sensitive crop parameters of cotton and it was found that base temperature, initial canopy cover, canopy growth coefficient (CGC), canopy decline coefficient (CDC), maximu m canopy cover and crop coefficient (K cb ) at canopy cover 100% were the most sensitive parameters for cotton. Calibration and validation of the model was preformed to study the suitability of the model for simulating yield and performance of cotton in the study area using the independent data sets from the experimental plots which was collected from Lungyaw cotton research farm in Kyaukse area for the years of 2005 - 2011. Three productivity indicators were used to evaluate the performance of rain - fed and ir rigated cotton in the study area. Water productivity was high in rain - fed cotton due to high effective rainfall and low in irrigated cotton due to less effective rainfall. Land productivity was found to be higher in irrigated cotton due to high yield and b iomass depending on the water available situational condition. Economic productivity was also found that it was higher in irrigated cotton due to high yield and low input costs. Economic analysis was performed by using partial budget analysis to find out t he most suitable economic condition for rain - fed and irrigated cotton cultivation. The irrigated cotton was found to be economically beneficial or gives higher returns to the farmers due to low input costs. Thus, the recommendation can be provided to show the advantages and disadvantages of improved practices under rain - fed and irrigated condition, in comparison with the farmer{u2019}s practices.
A thesis submitted in partial fulfillment of the requirements for t he degree of Master of Engineering in Water Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2013
Keywords: Cotton -- Myanmar; Irrigation water -- Myanmar